An Evaluation of Personal Cooling Systems for Reducing Thermal Strain Whilst Working in Chemical/Biological Protective Clothing - Bach, Aaron J. E.; Maley, Matthew J.; Minett, Geoffrey M.; Zietek, Stephanie A.; Stewart, Kelly L.; Stewart, Ian B. (Frontiers in Physiology, 2019)
The use of personal cooling systems to mitigate heat strain on first-responders achieves two potential performance benefits relative to the absence of such cooling: 1) the completion of a workload with less effort; and/or 2) the completion of a greater workload for the same effort. Currently, claims made by manufacturers regarding the capability of their products for use in conjunction with chemical/biological protective clothing remain largely unsubstantiated. The purpose of this investigation was to evaluate the means by which heat strain can be alleviated during uncompensable heat stress in chemical/biological clothing, using the ASTM F2300-10 methodology. Eight healthy males completed five trials of continuous walking (4.5km·h-1; 35°C; 49% RH) for up to 120min while wearing one of four cooling systems and/or a National Fire and Protection Association 1994 Class-3 chemical/biological ensemble. The four cooling methods (ice vest [IV], phase-change vest [PCM], water-perfused suit [WS] and combination ice slurry/ice vest [SLIV]) and no cooling (CON). We observed significant improvements in trial times for IV (18 ± 10min), PCM (20 ± 10min) and SLIV (22 ± 10min), but no differences for WS (4 ± 7min). Heart rate, rectal, mean skin and body temperatures were significantly lower in all cooling conditions relative to control at various matched time points in the first 60min of exercise. Thermal sensation, comfort and perceived exertion all had significant main effects for condition, and time, there were no differences in their respective interactions. The IV, PCM and SLIV produced lower heart rate, mean skin, rectal and mean body temperatures in addition to improved work times compared to control. The WS did not improve work times possibly as a result of the cooling capacity of the suit abating, and magnifying thermal insulation. Considering the added time and resources required to implement combination cooling in the form of ice slurry and ice vest (SLIV), there was no significant additive effect for perception, cardiovascular strain, rectal temperature and total trial time relative to the phase change vest or ice vest alone. This may be a product of a ‘ceiling’ effect for work limit set to 120min as part of ASTM F2300-10.